2016
DOI: 10.1002/ece3.2589
|View full text |Cite
|
Sign up to set email alerts
|

Functional community structure of African monodominant Gilbertiodendron dewevrei forest influenced by local environmental filtering

Abstract: Monodominant patches of forest dominated by Gilbertiodendron dewevrei are commonly found in central African tropical forests, alongside forests with high species diversity. Although these forests are generally found sparsely distributed along rivers, their occurrence is not thought to be (clearly) driven by edaphic conditions but rather by trait combinations of G. dewevrei that aid in achieving monodominance. Functional community structure between these monodominant and mixed forests has, however, not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 61 publications
9
65
2
Order By: Relevance
“…Our results therefore indicate that a similar advantage might apply to P as for N in promoting nutrient limitation in Gilbertiodendron and other ectomycorrhizal forests. Similarly, Kearsley et al () report lower bioavailable P in soil at 0–30 cm depth in Gilbertiodendron as compared to mixed forest for their DRC study site, and suggest that low concentrations of N and P in Gilbertiodendron leaves point to ectomycorrhizal‐mediated N and P limitation.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our results therefore indicate that a similar advantage might apply to P as for N in promoting nutrient limitation in Gilbertiodendron and other ectomycorrhizal forests. Similarly, Kearsley et al () report lower bioavailable P in soil at 0–30 cm depth in Gilbertiodendron as compared to mixed forest for their DRC study site, and suggest that low concentrations of N and P in Gilbertiodendron leaves point to ectomycorrhizal‐mediated N and P limitation.…”
Section: Discussionmentioning
confidence: 71%
“…Plasticity in light acquisition provides seedlings competitive advantage to recruit and release at different light levels; abundant large seedlings in the seedling bank help shape the light environment of smaller competitors. Citations in Figure: 1 Vierling and Wessman (); 2 Torti et al (), 3 Hart (); 4 Makana and Thomas (); 5 This study; 6 Newbery et al (); 7 Blake and Fay (); 8 Makana et al (); 9 Kearsley et al (); 10 Gérard (); 11 Cassart et al (); 12 Corrales et al (); 13 Phillips et al (); 14 Lin et al (); 15 Zhu et al (); 16 Averill and Hawkes () [Proposed mechanisms that have not been supported in studies: Makana and Thomas () found no evidence to support dense leaf litter preventing seedlings of other species to establish. Ebenye et al () found no evidence that EM hyphal networks facilitate nutrient exchange between adults and seedlings.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations